The Russian-Orthodox tradition and modernity - Buss, Andreas E. (Studies in the history of religions, 2003)
This work aims to identify the uniqueness of the Russian-Orthodox religious tradition and to contrast it with two of the characteristics of modern Western society - its particular economic ethics and individualism. Max Weber and Louis Dumont provide the theoretical framework.